Marked effects of Pilates on the abdominal muscles: a longitudinal magnetic resonance imaging study - Dorado, C.; Calbet, J. A. L.; Lopez-Gordillo, A.; Alayon, S.; Samchis-Moysi, J. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The study`s purpose was to analyze the effects of Pilates on the volume of the rectus abdominis (RA), obliques, and transversus abdominis, with the last two considered conjointly (OT).